To the question of the appointment of old Russian heraldic pend - Tsemushau, Stsiapan N. (Journal of the Belarusian State University. History, 2018)
The problem of the functional purpose of trapezoidal pendants, which are discovered by archaeologists in the territory of Eastern Europe and dated to the X–XI centuries, is considered. Metal or (more rarely) bone pendants contain images of princely patrimonial signs that make it possible to ascertain their attribution – belonging to the rulers of the Old Russian state, known from chronicle sources. The appearance of trapezoidal pendants is associated with the functioning of one of the branches of public administration – the tax-tributary system. Pendants acted as a kind of «credentials» representatives of the prince’s administration, who entered into relations with the local population as judges and tax collectors, that is, in those areas that belonged to the number of princely powers. The termination of the use of trapezoidal pendants must be associated with changes that occurred in the form of the state structure of the Old Russian state and at the same time in the organization of the collection of material goods from the subordinate population. Images of princely signs on pendants allow you to draw certain conclusions about the features of the implementation of management in the territory of Ancient Rus.
Keywords: Ancient Rus’; public administration; tax-tributary (fiscal) system; princes of Rurikids; trapezoidal pendants; patrimonial signs; signs of ownership (tamghi); danniki and virniki